1988
DOI: 10.1007/bf00279665
|View full text |Cite
|
Sign up to set email alerts
|

Motion perceptions induced by off-vertical axis rotation (OVAR) at small angles of tilt

Abstract: Off-vertical axis rotation in darkness induces a perception of body motion which lasts as long as rotation continues. Perceived body motion is the combination of two simultaneous displacements. The most easily perceived is a translation without rotation along a conical path, at the frequency of the actual rotation. Meanwhile, the subjects feel as if they were always facing towards the same direction. The summit of the cone is generally below the head, from the waist to below the feet, and subjects have a sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 7 publications
5
42
0
Order By: Relevance
“…Because of the tilted axis, head orientation changes continuously with respect to gravity, as the body alternates between roll and pitch tilt. In a recent study (Vingerhoets et al 2006), following up on earlier investigations by Denise et al (1988) and Guedry (1974), we showed that the initially veridical rotation percept during prolonged OVAR decays gradually (Fig. 2B) and that a percept of circular head translation against the actual direction of movement emerges concurrently (Fig.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Because of the tilted axis, head orientation changes continuously with respect to gravity, as the body alternates between roll and pitch tilt. In a recent study (Vingerhoets et al 2006), following up on earlier investigations by Denise et al (1988) and Guedry (1974), we showed that the initially veridical rotation percept during prolonged OVAR decays gradually (Fig. 2B) and that a percept of circular head translation against the actual direction of movement emerges concurrently (Fig.…”
Section: Introductionsupporting
confidence: 57%
“…In an earlier OVAR study, Denise et al (1988) reported that their subjects felt being in the nose-up position 0 to 50°before they actually reached this position, which indicates a perceptual phase lead. By contrast, as shown in Fig.…”
Section: Evaluation Of the Combined Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…Verbal reports of the perceived motion path were consistent across CW and CCW directions of rotation, and are therefore combined in Table 1. During OVAR at 10° tilt, all subjects reported the pattern of body motion previously described by Denise et al (1988): progression along a conical path while facing the same direction. For 20° tilt at 0.125 Hz, 79% of subjects continued to perceive a conical path.…”
Section: Resultsmentioning
confidence: 99%
“…A tilt angle of 10° was also tested during 0.125 Hz rotation, which allowed a direct comparison of our motion perception results with those previously obtained by Denise et al (1988).…”
Section: < Insert Figure 1 About Here> Proceduresmentioning
confidence: 97%